STUDI EKSPERIMENTAL PERILAKU GESER MURNI DENGAN SENGKANG SAMBUNGAN MEKANIS DAN LAS - Doni Apriadi Putera; S. Wisnu B.; Han Ay Lie; Sukamta Sukamta (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2012)
Shear reinforcement in reinforced concrete structures or stirrups are customarily fabricated with a hook, attaching the two ends at one of the corners of the member. This process is a result of mechanical bending and widely recognized as a mechanical connection. In addition to this type of connection, welding is an alternate method to fabricate the connection of the stirrups’ ends. In the case of welding, the placing of the joint can either be at a corner, or at mid height of the stirrup. This research work objective is to investigate the influence of mechanical connections as compared to welded joints in shear reinforcing stirrups. The placement aspect of the welded connection is also studied. Further, this research work also endeavors to assess as whether the shear strength obtained by pure shear research that has been done before. The study showed that the stirrup’s connection type and positioning, affects the overall shear strength of the concrete specimens. Stirrups welded at the corners exhibit the highestshear capacity. Close observation and analysis suggested that this result is due to the higher stiffness of this type of connection, as compared to the joints placed at mid height. Further, the test results showed that the coefficient obtained in this study approached the coefficients obtained from a previous study of pure shear. The main reason for obtaining the coefficients of the various possible because of the difficulty of determining exactly concrete resistance to pure shear.